A preliminar overview of species composition and geographical distribution of Malvinian weevils (Insecta: Coleoptera: Curculionidae) - Posadas, Paula (Zootaxa, 2008)
The objective of this paper is to provide an integrative approach to species composition and distributional information on the weevil fauna of Islas Malvinas (Falkland Islands). A total of 22 species belonging to 11 Curculionidae genera are recorded for the archipelago. Four of these genera belong to Entiminae (i.e., Caneorhinus, Cylydrorhinus, Malvinius, and Morronia) and the remaining seven belong to Cyclominae (i.e., Antarctobius, Falklandiellus, Falklandius, Germainiellus; Haversiella, Lanteriella, and Puranius). The Malvinian weevil fauna could be considered as an impoverished version of that from Tierra del Fuego at the generic level, but with a very high degree of species level endemism. The Malvinian weevil fauna exhibits a great linkage to that from southernmost South America. It has been postulated that the evolution of Malvinian weevil fauna responded to several geodispersal and subsequent vicariant events which determined the archipelago´s alternative connections and disconnections from southern South America. These events were due to sea-level variations induced by glacial-eustatic agents during Tertiary and Quaternary times. Finally, synonymic lists are provided for each species known to occur on the islands. Also, distributional data for each species are mapped and keys and illustrations are presented to identify weevil taxa recorded for the Islas Malvinas.